Manner of death : a novel - Cook, Robin, 1940- (G.P. Putnam's Sons, 2023)
"After Dr. Jack Stapleton's near-death confrontation with a medical serial killer, his wife, NYC Chief Medical Examiner Laurie Montgomery, is carrying the load both at home and at work. When Laurie insists Dr. Ryan Sullivan--an underperforming senior pathology resident who is spending his required month at the medical examiner's office but who truly detests doing forensic autopsies--assist her on a suicide autopsy in the hopes of stimulating his interest in the field, the last thing she expects is to be unwittingly drawn into a major conspiracy that puts her own life in jeopardy, Desperate to avoid performing as many forensic autopsies as possible, Dr. Ryan Sullivan offers to participate in a research project on a series of suicides put together by one of the medical legal investigators. These suicides, like the case Ryan analyzes with Laurie, hint at some bothersome questions about their 'manner of death.' Although the project was more of a ruse than a serious study, Ryan surprise himself by immediately uncovering unexpected shared commonalities. Most astonishing of all, Ryan's inquiries eventually put him and Laurie at risk by leading to a nefarious cancer diagnostics company that promotes the very latest, groundbreaking cancer-screening technology in a shockingly self-serving and fraudulent fashion"--Dust jacket flap.